1996
DOI: 10.2166/wst.1996.0702
|View full text |Cite
|
Sign up to set email alerts
|

Operational efficiency of a pilot plant for wastewater reuse

Abstract: Reuse of wastewaters for non-potable uses needs a higher than normal reliability in treatment plant operation and management, in order to ensure higher safety margins for public health and environmental protection. After a two-years research project on a pilot plant designed for agricoltural reuse, all control parameters used for the plant operation have been examined, in order to obtain useful observations on efficiency of each of the treatment units, for best overall performance. It was concluded that this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The institutionalisation of centralised approaches is also a crucial factor. Technology has however, progressed, and small-scale treatment is now capable of reliably and consistently producing high quality effluents (Croce et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The institutionalisation of centralised approaches is also a crucial factor. Technology has however, progressed, and small-scale treatment is now capable of reliably and consistently producing high quality effluents (Croce et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that more than half of the 667 cities in China are facing water shortage (He et al, 2001). What's more, industrialization and urbanization have accelerated pollution in the water environment (Christova-Boal et al, 1996), making water a limited resource, especially in northern China, and thus great attention is being paid to the reclamation and reuse of treated water discharged from municipal or industrial wastewater treatment plants (WWTPs) (Croce et al, 1996;Aramaki et al 2001;Eriksson et al, 2002;Fane et al 2002). Advanced/ tertiary plays a critical role in the effective treatment of municipal and industrial wastewater to meet water quality objectives for water reuse and to protect public health.…”
Section: Introductionmentioning
confidence: 99%